The Use of the Tic-Tac-Toe Game-Based Learning on Students’ Vocabulary Mastery - Syamsiarna Nappu; Risnawati; Hasnawati (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The research aimed to analyze improvements in English vocabulary mastery among eighth-grade students through game-based learning using the Tic-Tac-Toe. One of the fundamental elements in learning the target language, English as a Foreign Language (EFL), is vocabulary, but quite often junior high school students are not able to identify words by their meanings or word classes, or even use them properly in simple communicative contexts. This research used a one–group pre–test–post–test design involving 30 VIII students from a Junior High School in Gowa Regency, Indonesia. The rationale for selecting these participants is based on preliminary classroom observations indicating that these students need extra assistance with vocabulary acquisition. A teacher-made vocabulary test consisting of multiple-choice and fill-in-the-blank vocabulary assessment was administered prior to the start of and following 6 Tic-Tac-Toe meetings. The intervention only included nouns, verbs, and adjectives from words referring to topics with which students already had some familiarity. The results showed that the overall mean score increased from 34.50 on the pre-test to 80.50 on the post-test, with gains that take on greater meaning when examining nouns, verbs, and adjectives, respectively. At the level, the t-test value (5.51) was greater than the t-table value (2.045). 05 significance level, suggesting a statistically sound improvement. This analysis demonstrates that Tic-Tac-Toe can serve as an affordable and interactive classroom strategy to reinforce vocabulary mastery, especially when teachers are seeking non-digitally dependent, offline learning activities.